Assessment of teaching and learning burn treatment basics among medical students - Geiza Máximo; Aline Ferrari Martins; Luís Ricardo Martinhão Souto (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Burns, an injury of high biopsychosocial importance, are a crucial issue in medical training, and newly graduated students face burn patients in a variety of professional settings. METHODS: This study assessed the teaching and learning of burns among medical students at a public facility in the State of São Paulo; a specific questionnaire was applied to evaluate first year (Group 1: 54 students) and sixth year (Group 2: 60 students) medical students' knowledge about the initial care of burn patients. RESULTS: In Group 1, there was a substantial lack of knowledge about the subject, with a general average incorrect answer rate ("errors") of 70.98% and a correct answer rate of 29.02%; in Group 2, these rates were 36.66% and 63.34%, respectively. Only 63.34% of the sixth-year students would be able to adequately conduct the treatment of a burn patient, gauged by their ability to offer a patient a better prognosis. CONCLUSIONS: The data are disturbing, since adequate knowledge and preparation of the trainees for the care of burn patients has not been verified, and burns are emergency situations that require prompt, adequate, and efficient medical intervention to reduce patients' morbidity and mortality.